A systematic review of health communication strategies in Sub-Saharan Africa-2015-2022 - Adewale Olaoye; Kevin Onyenankeya (Tabriz University of Medical Sciences, 2023)
Background: Health communication strategies have become critical in managing public health issues across sub-Saharan Africa. In the literature, health communication strategies have been well documented. The studies are often narrow, focusing on individual countries or specific health issues. No research documented and consolidated the health communication strategies across sub-Saharan Africa. This review attempts to catalogue prevalent health communication strategies, how the various countries have implemented these strategies and the barriers to effective health communication practices in Africa. Methods: We systematically reviewed existing literature on health communication strategies in sub-Saharan Africa to answer formulated questions. A Google search was performed in October 2022 with the keywords 'health communication', 'strategies', 'promotion,' 'education,' and 'engagement,' The data reported in this article included evidence published between 2013 and 2023. Selected documents were content analyzed, and significant sections were mapped against specific strategies/themes. These subsets of data were used to present the results and analysis. Results:The review indicates that different health communication strategies have been deployed across Africa. In some countries, specific strategies are used to tackle specific health issues, while a combination of strategies is used in others. In some countries, the strategies are unclear, and implementation is improvised, sometimes misapplied, or truncated by bureaucratic red tape and incompetence. The prevalent strategies are mainly those prescribed from outside with little input from the beneficiaries. Conclusion: The review suggests that using a holistic or multi-pronged health communication approach that is context-specific and participatory could attract more uptakes of health messages.